Effect of endogenous hydrogen sulfide on the transwall gradient of the mouse colon circular smooth muscle. (5th February 2014) - Sha, L.; Linden, D. R.; Farrugia, G.; Szurszewski, J. H.
Abstract : Key points: A CO‐dependent transwall gradient of resting membrane potential exists across the circular muscle layer in the gastrointestinal tract; this gradient regulates the strength of phasic muscle contraction during electrical slow wave activity. H2 S, CO and NO are endogenously generated in the muscle layers of the gut wall. Inhibiting the H2 S producing enzyme CSE with the CSE inhibitor PAG had no significant effect on transwall resting membrane potential gradient in control preparations but significantly shifted the entire gradient in the depolarizing direction in preparations pretreated with the NO synthase (NOS) inhibitorl ‐NNA. PAG significantly shifted the gradient in the depolarizing direction in mouse preparations lacking neuronal NOS (nNOS‐KO) and the gradient was significantly shifted in the depolarizing direction in mouse preparations lacking both nNOS and CSE (CSE‐KO–nNOS‐KO). NO production was significantly higher in CSE‐KO mouse preparations compared to wild‐type mouse preparations and the amplitude of NO‐mediated slow inhibitory junction potentials (S‐IJPs) was significantly higher in CSE‐KO mouse preparations compared to the amplitude of S‐IJPs in wild‐type mouse preparations. Nearly all submucosal neurons and myenteric neurons were CSE positive and 11% of submucosal neurons and 50% of myenteric neurons were nNOS positive. Our novel findings suggested that endogenous H2 S is a stealth hyperpolarizing factor on smooth muscle cells and that endogenous H2 S inhibits NO production from nNOS. Abstract: A transwall gradient in resting membrane potential (RMP) exists across the circular muscle layer in the mouse colon. This gradient is dependent on endogenous generation of CO. H2 S is also generated in muscle layers of the mouse colon. The effect of endogenously generated H2 S on the transwall gradient is not known. The aim was to investigate the role of endogenous H2 S. Our results showed that the CSE inhibitordl ‐propargylglycine (PAG, 500 μm ) had no effect on the transwall gradient. However, in preparations pretreated with the nitric oxide synthase inhibitor N ‐nitro‐l ‐arginine (l ‐NNA, 200 μm ) and in nNOS‐knockout (KO) mouse preparations, PAG shifted the transwall gradient in the depolarizing direction. In CSE‐KO–nNOS‐KO mice, the gradient was shifted in the depolarizing direction. Endogenous generation of NO was significantly higher in muscle preparations of CSE‐KO mice compared to wild‐type (WT) mice. The amplitude of NO‐mediated slow inhibitory junction potentials (S‐IJPs) evoked by electric field stimulation was significantly higher in CSE‐KO mouse preparations compared to the amplitude of S‐IJPs in wild‐type mouse preparations. CSE was present in all submucosal ganglion neurons and in almost all myenteric ganglion neurons. Eleven per cent of CSE positive neurons in the submucosal plexus and 50% of CSE positive neurons in the myenteric plexus also contained nNOS. Our results suggest that endogenously generated H2 S acts as a stealth hyperpolarizing factor on smooth muscle cells to maintain the CO‐dependent transwall gradient and inhibits NO production from nNOS.